Paternal chromosome incorporation into the zygote nucleus is controlled by maternal haploid in Drosophila. - Loppin, B.; Berger, F.; Couble, P. (Developmental Biology, 2001)
maternal haploid (mh) is a strict maternal effect mutation that causes the production of haploid gynogenetic embryos (eggs are fertilized but only maternal chromosomes participate in development). We conducted a cytological analysis of fertilization and early development in mh eggs to elucidate the mechanism of paternal chromosome elimination. In mh eggs, as in wild-type eggs, male and female pronuclei migrate and appose, the first mitotic spindle forms, and both parental sets of chromosomes congress on the metaphase plate. In contrast to control eggs, mh paternal sister chromatids fail to separate in anaphase of the first division. As a consequence the paternal chromatin stretches and forms a bridge in telophase. During the first three embryonic divisions, damaged paternal chromosomes are progressively eliminated from the spindles that organize around maternal chromosomes. A majority of mh embryos do not survive the deleterious presence of aneuploid nuclei and rapidly arrest their development. The rest of mh embryos develop as haploid gynogenetic embryos and die before hatching. The mh phenotype is highly reminiscent of the early developmental defects observed in eggs fertilized by ms(3)K81 mutant males and in eggs produced in incompatible crosses of Drosophila harboring the endosymbiont bacteria Wolbachia.